1995
DOI: 10.1111/j.1745-4557.1995.tb00386.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP OF NITROGEN‐SULFUR FERTILIZATION AND HYBRID TO SENSORY CHARACTERISTICS OF shrunken2 SWEET CORN KERNELS

Abstract: Sweet corn hybrids significantly affected the primary components of eating quality, i.e. sweetness (P Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Acting through a heat-labile S-containing amino acid precursor, S-methylmethionine sulfonium salt (MMS), DMS is the compound responsible for the characteristic odor of cooked sweet corn (Bills and Keenan, 1968;Williams and Nelson, 1974). Although not as easily defined as either sweetness or texture, sensory evaluation studies have shown that aroma can contribute between 15% and 33% of the overall flavor response in sweet corn (Flora and Wiley, 1974a;Wong et al, 1995).…”
mentioning
confidence: 99%
“…Acting through a heat-labile S-containing amino acid precursor, S-methylmethionine sulfonium salt (MMS), DMS is the compound responsible for the characteristic odor of cooked sweet corn (Bills and Keenan, 1968;Williams and Nelson, 1974). Although not as easily defined as either sweetness or texture, sensory evaluation studies have shown that aroma can contribute between 15% and 33% of the overall flavor response in sweet corn (Flora and Wiley, 1974a;Wong et al, 1995).…”
mentioning
confidence: 99%